Analisis SOAR dalam Menentukan Strategi Pelayanan Pasca Diklat Penguatan Kepala Sekolah di BPSDM Provinsi DKI Jakarta - Agus Kurniati; Sopan Adrianto (Cendekia Niaga, 2021)
In organizing School Principal Strengthening Training, BPSDM Province DKI Jakarta is required to produce graduates capable of compiling RPS document in order to improve education quality. The problem faced was the large number of graduates who have difficulties during the preparation of RPS document and they need guidance to arrange RPS document, so that the resulting RPS document can be implemented properly in order to improve education quality. One of the strategic step taken is through post training services. This study is aimed to analyze the post training strategy of Strengthening School Principal Training using SOAR strategy analysis. The research method used is descriptive quantitative. Data collection was carried out through interview, observation and questionnaire. The data obtained were processed and tabulated as a basis for conducting SOAR analysis. The analysis used SOAR analysis by calculating the IFE-EFE matrix. Based on the result of the SOAR analysis, BPSDM Province DKI Jakarta is in the quadrant III/OA strategy quadrant, which is to take advantage of existing opportunities to achieve the expected result through a strategy for making forum/media in order to optimize and maintain the competence of Training graduates, namely the School Principal Managerial Consultation Room.